Transit of Russian gas across Ukraine: Conditions for post-2024 continuation - Katja Yafimava (The Oxford Institute for Energy Studies, 2024)
On 1 January 2025, the Transit Agreement, which has provided political, commercial, technical and legal grounds for the transit of Russian gas across Ukraine during 2020-24, will expire. Once it happens - and if no extension or alternative transit arrangement are agreed - the transit will stop. The Ukrainian government has repeatedly stated that it will not extend the Agreement because of its unwillingness to have a direct relationship with the Russian government and Gazprom as long as the armed conflict between two countries continues. The EC has asserted that the EU is 'ready to live' without Russian gas that is still transiting Ukraine - 14 bcm in 2023 - and that it will not put pressure on Ukraine to renew the Agreement. The Russian government has stated that it will provide the gas for delivery across Ukraine if a legal framework for transit will be put in place. While at the time of this paper going into print no such framework has been agreed - and neither the EC nor the Ukraine government statements bode well for this to happen - nonetheless, transit stoppage is not yet a foregone conclusion. This paper concludes that at a minimum the following conditions would have to be met for continued post-2024 transit to be possible: political support from EU Member States which would be most affected by potential transit cessation (particularly Slovakia and Austria) for their buyers' efforts to reach an agreement on continued transit enabling them to book capacity in the Ukrainian gas transmission system at the Ukraine-Russia border; clearly communicated lack of objection on the part of the EC for these Member States and their gas buyers to do so; most importantly, Ukraine's willingness to transit Russian gas as confirmed by signature (or renewal) of the technical interconnection agreement between the Ukrainian Transmission System Operator (GTSOU) and Gazprom.
Keywords: 330; Austria; Azerbaijan; capacity booking; EC; Gazprom; GTSOU; Hungary; MVM; Naftogaz; OMV; Post-2024 transit; REPowerEU; Russia; security; Slovakia; SOCAR; SPP; transit agreement; transit cessation; TurkStream; Ukraine